A High Resolution Melting Analysis (HRM) PCR assay for the detection and identification of Old World Leishmania species - Saadi-Ben Aoun, Yusr; Souguir, Hejer; Chouaieb, Hamed; Kraiem, Mongia; Bel Hadj Ali, Insaf; Chakroun, Ahmed S.; Noguier, Florian; Fathallah-Mili, Akila; Piquemal, David; Guizani, Ikram (PLOS Neglected Tropical Diseases, 2024)
Background Cutaneous Leishmaniases (CL), highly endemic in Africa and Mediterranean region, are caused by different Leishmania parasite species. Accurate species identification is crucial for effective diagnosis, treatment, and control of these diseases, but traditionally relies on DNA-based methods. High Resolution Melting analysis PCR (HRM PCR) provides rapid results and precise differentiation based on nucleotide variations. We hypothesized that the Strumpellin gene of Leishmania could serve as an effective target for developing a HRM PCR method for the rapid and efficient detection and identification of Leishmania species in CL diagnosis. Methodology The Strumpellin gene was investigated in Trypanosomatidae family using bioinformatics and phylogenetic approaches to explore its evolutionary conservation and suitability for HRM PCR. HRM PCR target and primers were selected and validated on 73 different Leishmania DNAs. The analytical limit of detection was assessed, and the performance for detecting and identifying parasites in 38 cutaneous lesions aspirates was compared to Direct Examination (DE) and ITS1-PCR RFLP methods. Findings The developed HRM PCR assay accurately identified promastigote DNAs of L. donovani/L. infantum, L. major, L. aethiopica, L. turanica, L. arabica, L. tarentolae and 3 genotypes of L. tropica. Differentiation was achievable with as little as a single nucleotide difference occurring within or between species. HRM profile interpretations were consistent with sequencing results of the HRM PCR target and identification by ITS1-PCR RFLP. The assay could detect the equivalent of 24 Leishmania parasites. In a small-scale sample, we brought proof of principle demonstration the HRM could detect and identify Leishmania in human cutaneous samples. In comparison to DE, the sensitivity and specificity of the HRM PCR assay on human cutaneous samples were 88% and 84.62%, respectively, while the ITS1-PCR assay evaluation parameters were 84% and 92.31%. Statistical analysis confirmed good correlation among the three tests, with both molecular methods providing congruent parasite identification. Notably, in three samples, only the HRM PCR assay was able to assign them to L. infantum or L. tropica. Conclusions The HRM PCR assay is a valuable tool for the detection and identification of Old World Leishmania species. Its integration into molecular diagnostic algorithms for CL or in eco-epidemiological studies holds promise for improving disease management and control.